ISOLATION AND IDENTIFICATION MOMORDICIN I FROM LEAVES EXTRACT OF Momordica charantia L. - Purnawati, N. M. (Jurnal Kimia (Journal of Chemistry); Vol. 2, No. 1 Januari 2008)
Momordicin I has been isolated from dichloromethane extract of leaves Momordica charantia, L. The isolation was done by fractionation the dichloromethane extract followed by bioassay using artemia salina,L larvae. The crude extract was fractionated through reverse phase column chromatography (C18 Sep-Pak) with eluotropic series solution of MeOH: H2O (0-100% MeOH). The most active fraction, F9 (80% MeOH-20% H2O) was purified by recrystallisation from chloroform to yield a white crystal melted at 125-128oC. The structure of the active compound was determined by interpretation of the spectral data (IR, 1HNMR, 13CNMR, DEPT, HCOSY, HMCOSY, HMBC and MS) and its structure was elucidated as 3,7,23-trihydroxycucurbitan-5,24-dien-19-al which is known as momordicin I.
Keywords: isolation and identification, momordicin I, Momordica charantia L., Artemia salina L.